Study of landfill leachate as a sustainable source of water and nutrients for algal biofuels and bioproducts using the microalga Picochlorum oculatum in a novel scalable bioreactor. (June 2019) - Dogaris, Ioannis; Loya, Bethany; Cox, Jeffrey; Philippidis, George
Graphical abstract: Highlights: Landfill leachate proved an alternative low-cost water source to grow algae. Microalgae were cultivated outdoors using a novel scalable horizontal bioreactor. High cell density cultures of the microalga Pichochlorun oculatum achieved. The generated algal biomass was suitable for biofuel production. Abstract: High water demand is a major challenge for the algae industry, so cultivating algae in wastewater can have the double benefit of biomass production and water remediation. The use of landfill leachate (LL), which is wastewater generated in landfills, was investigated to grow the microalga Picochlorum oculatum in a novel horizontal bioreactor (HBR), a low-cost modular cultivation system that reduces water evaporation and contamination risk thanks to its enclosed design. Pilot-scale (150 L) and commercial-scale (2000 L) HBRs that were operated outdoors in Florida using LL in batch and semi-continuous modes generated high cell density cultures (1.7·10 9  cells mL −1 ) and reached up to 1.9 g L −1 of dry biomass suitable for biofuel production. Demonstrating the ability of ample non-potable water sources, such as LL, to support algae cultivation is essential for improving the sustainability and cost-effectiveness of commercial algal biofuels and bioproducts, as freshwater resources become increasingly scarce.